Hubungan Pola Asuh Orang Tua dan Teman Sebaya Dengan Perilaku Merokok Pada Siswa di SMK Negeri 3 Kota Sorong - Nompo, Rifki Sakinah; Fitriani, Fitriani; Fatimah, Fatimah; Tamaela, Josepha Mariana; Larat, Tanaya Pratiwi (Jurnal Keperawatan Komplementer Holistic, 2025)
Indonesia is ranked third globally in terms of the highest number of smokers, with adolescents being among the most at-risk groups. Social influences, including parenting style and peer pressure, are seen as major contributors to smoking behavior. This study aimed to examine the connection between parenting styles and peer influence with smoking behavior among students at SMK Negeri 3 Kota Sorong. A quantitative correlational approach using a cross-sectional design was employed. The study involved 77 students from grade XI selected through non-probability sampling. Questionnaires covering parenting styles, peer influence, and smoking behavior were used as research instruments. Data were analyzed using the chi-square test. The results indicated no significant relationship between parenting style and smoking behavior (p = 0.770), but a significant relationship was found between peer influence and smoking behavior (p = 0.040). These findings suggest that peer influence plays a substantial role in adolescent smoking behavior, while parenting style does not show a significant effect. Peer-based interventions are therefore suggested to help reduce smoking rates among youth.